Weaving mini-stories: aesthetic education in participatory approaches in early childhood education (Olhar de Professor, 2025)
The estudy presents a report of experience in Early Childhood Education, focusing on participatory research aimed at 2-year-olds. The pedagogical proposal starts from the observation of children’s interests and curiosities to develop a project focused on modeling with clay, integrating games and interactions that stimulate imagination and creativity. The work highlights the importance of an aesthetic look throughout the educational process, from the choice of materials to the organization of space. Children were encouraged to explore the materiality of clay, promoting meaningful learning through sensory and aesthetic experiences. The teachers followed and documented these experiences, developing mini-stories to record the discoveries and learning. This process of knowledge construction allowed to reflect on the relationship between ethics, aesthetics and orality, besides emphasizing the child’s role in school.
Keywords: Early Childhood Education; Participatory research; Mini-stories; Joint work